Youth unemployment in Europe and the United States - David N. F. Bell; David G. Blanchflower (Institute for the Study of Labor (IZA), 2011)
This paper focuses particularly on youth unemployment, why we should be concerned about it, why it is increasing again, how the present difficulties of young people entering the labour market differ from those of the past and what useful lessons have been learned that may guide future policy. We focus on Europe and USA, but introduce evidence from other countries where appropriate. Our analysis of the UK NCDS birth cohort data provides evidence supporting the notion that early adulthood unemployment creates long lasting scars which affect labour market outcomes much later in life. Our chosen variables are weekly wages and happiness. Our results show significant effects at age 50 from early adulthood unemployment. These affects are stronger than more recent unemployment experiences.
urn:nbn:de:101:1-201105173099
Keywords: J31; J64; 330; youth unemployment; scarring effects; happiness; Jugendarbeitslosigkeit; Erwerbsverlauf; Lohn; Zufriedenheit; Schätzung; Europa; USA